Important Aspects of Nutrition in Children with Cancer - Bauer, Jacqueline (American Society for Nutrition, 2011)
Adequate nutrition during cancer plays a decisive role in several clinical outcome measures, such as treatment response, quality of life, and cost of care. However, the importance of nutrition in children and young adults with malignancies is still an underestimated topic within pediatric oncology. The importance of our work is to reinforce and indicate that malnutrition in children with cancer should not be accepted at any stage of the disease or tolerated as an inevitable process. Unique to our manuscript is the close collaboration, the exchange of knowledge and expertise between pediatric oncologists and a nutritional specialist, as well as the comprehension of the mechanisms during cancer cachexia and malnutrition. We provide a critical review of the current state of research and new knowledge related to nutritional management in childhood cancer.